Tourism Institutional Collaboration in Management of the Setu Babakan Betawi Cultural Village, Jakarta - Masyhari Makhasi, Ghifari Yuristiadhi; Zaman, Shabrina Nurhanin Putri; Rahmatullah, Muhammad Fauzan; Hutabarat, Yusuf Junifer; Supranta, Virginia Amelia (Sekolah Vokasi, Universitas Gadjah Mada, 2023)
Tourism institutions are organizations involved in tourism development in a destination. The interactions between tourist institutions are frequently characterized by dynamism, leading to the emergence of favorable collaborations as well as unfavorable conflicts. A plethora of research has been conducted on tourism institutions, but, the majority of these studies have focused mostly on rural regions. This study provides a new perspective on analyzing models of institutional tourism partnership in urban settings, focusing on a case study conducted in the Setu Babakan Betawi Village in South Jakarta. This study, employing data from interviews with local community, observation, and secondary sources, determined that the collaboration among local communities, regional government, community organizations, and the private sector produced a beneficial synergy for the Setu Babakan Betawi Village destination, leading to its success in winning the 2021 Indonesia Tourism Village Awards. The findings of this study have practical applications for rural areas and other tourist destinations, highlighting the critical need for collaboration among tourism institutions to promote local tourism based on cultural potential.